2012
DOI: 10.1038/tp.2012.85
|View full text |Cite
|
Sign up to set email alerts
|

Replication and meta-analysis of TMEM132D gene variants in panic disorder

Abstract: A recent genome-wide association study in patients with panic disorder (PD) identified a risk haplotype consisting of two single-nucleotide polymorphisms (SNPs) (rs7309727 and rs11060369) located in intron 3 of TMEM132D to be associated with PD in three independent samples. Now we report a subsequent confirmation study using five additional PD case–control samples (n=1670 cases and n=2266 controls) assembled as part of the Panic Disorder International Consortium (PanIC) study for a total of 2678 cases and 3262… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 16 publications
2
55
0
2
Order By: Relevance
“…Risk genotypes were associated with higher TMEM132D mRNA expression in human postmortem frontal cortex, results further supported by a mouse model in which high anxiety-related behavior was associated with a Tmem132d SNP and correlated with expression of Tmem132d mRNA in the anterior cingulate cortex (Erhardt et al, 2011). In a subsequent meta-analysis of eight independent case-control samples, genome-wide significant associations of rs7309727 and the haplotype of rs7309727-rs11060369 were reported when the analysis was restricted to European ancestry cases with primary PD (Erhardt et al, 2012). The function of this gene is not fully understood, but it has been suggested that it has a role in threat processing (Haaker et al, 2014).…”
Section: Common Genetic Variationmentioning
confidence: 68%
“…Risk genotypes were associated with higher TMEM132D mRNA expression in human postmortem frontal cortex, results further supported by a mouse model in which high anxiety-related behavior was associated with a Tmem132d SNP and correlated with expression of Tmem132d mRNA in the anterior cingulate cortex (Erhardt et al, 2011). In a subsequent meta-analysis of eight independent case-control samples, genome-wide significant associations of rs7309727 and the haplotype of rs7309727-rs11060369 were reported when the analysis was restricted to European ancestry cases with primary PD (Erhardt et al, 2012). The function of this gene is not fully understood, but it has been suggested that it has a role in threat processing (Haaker et al, 2014).…”
Section: Common Genetic Variationmentioning
confidence: 68%
“…The function of TMEM132D still remains to be confirmed but there is some suggestion of its involvement in neuronal sprouting and brain connectivity (Erhardt et al, 2012). Significant effects at p < .05 were also identified for the 5-HTTLPR genetic variant in OCD as listed in Supplementary Table 1.…”
Section: Anxiety Disorder (Ad)mentioning
confidence: 91%
“…Strong gene effects (p < .001) were also identified for 2 variants of the TMEM132D gene: the rs7309727 T allele and the rs11060369 A allele in predicting PD in mixed/Caucasians (Erhardt et al, 2012). The function of TMEM132D still remains to be confirmed but there is some suggestion of its involvement in neuronal sprouting and brain connectivity (Erhardt et al, 2012).…”
Section: Anxiety Disorder (Ad)mentioning
confidence: 92%
“…13,14 A recent genome-wide copy number variation study also found an excess of common duplications in a region on 16p11.2. 15 Genome-wide association (GWA) studies of PD [11][12][13][14][15][16][17][18][19][20][21] have not yet established risk loci, though 1 genetic 12,14,22,23 and functional 12,22 data have recently implicated variation in TMEM132D.…”
Section: Introductionmentioning
confidence: 99%